Small Bowel Ischemia due to Jejunum Volvulus in Pregnancy: A Case Report - Ioannis Vassiliou; Aliki Tympa; Michalis Derpapas; Georgios Kottis; Nikolaos Vlahos (Case Reports in Obstetrics and Gynecology)
The diagnosis of intestinal obstruction in pregnancy is difficult, as the symptoms may mimic pregnancy-associated complaints. The surgical management is challenging, as the mortality rate of midgut volvulus in pregnancy is high. We report the case of a 35-year-old woman at 21 weeks and 5 days of gestation with small bowel obstruction who presented to our institution with a 24 h history of colicky abdominal pain and nausea and who finally had a successful open repair.